REKONSTRUKSI WAJAH FORENSIK : MEMBANGUN WAJAH DARI TENGKORAK - Lenny Setiawati; Nabila maudy Salma; Anggun Lestary Husein (Jurnal Akta Trimedika, 2025)
Forensic facial reconstruction is an attempt to recreate the face of a deceased person from their skull remains. Forensic facial reconstruction is an alternative identification method that is widely used in the field of forensics to identify the unidentified remains. It also popular in the field of archeology to bring back the appearance of people in the past. Unfortunately, in Indonesia forensic facial reconstruction is not yet popular. In fact, forensic facial reconstruction can be quite cheap and accurate methods, as well as can be applied when other methods are not possible. There are several techniques using antemortem photos to three-dimensional techniques including manual and computerized. The two-dimensional technique using antemortem photo usually used for very fragile skull that is impossible to reconstruct manually in three-dimensional. The manual three-dimensional techniques make it possible to see the realistic face but time consuming to make. However, technological developments have been able to create computerized three-dimensional techniques that are faster and cheaper. This review will discuss forensic facial reconstruction in general and the role of the skull and soft tissue  in the final results. By involving knowledge in the field of facial bone and soft tissue anatomy, then equipped with anthropometric data corresponding to the skull, the final results will vary personally depend on the shape of the skull bones. Meanwhile, a touch of art will complete the appearance to make it more  real. Ultimately, the results of forensic facial reconstruction are a synergy between science and art.